Human Resource Management in Construction - A comparison with Traditional Approach - Anoop Kumar, V.; Ganesan, Dr. R. (Journal of Contemporary Research in Management (JCRM), 2013)
Effective utilization of Human Resource is one of the most important factor for the efficient and profitable functioning of any organization. It has special significance in the management of human resources in the construction process. The ancient Indian architecture gives guidelines to the scientific and systematic procedures for the construction of a building. Any person who wishes to construct a building should take the advice of a noble person, well versed in the science of building related topics, called Acharya. The Acharya’s advice will be proper and unbiased because he is endowed with all good qualities. In the design of building, the owner (Yajamana), the adviser (Acharya), and the master builder (Stapathi) have specific roles. This paper tries to find out the possibilities of incorporating the traditional process for getting things done in construction industry.